The Impact of Brexit on the Education Sector in the United Kingdom: A Comprehensive Analysis - Charkaoui, Hadil (Eximia, 2023)
This paper presents a comprehensive analysis of the effect of Brexit on the education sector in the United Kingdom. As the UK’s withdrawal from the European Union (EU) has unfolded, it has triggered substantial shifts and uncertainties across various domains, including education. This study aims to evaluate the repercussions of Brexit on key aspects of the education sector, including student mobility, research collaborations, funding opportunities, curriculum development, and institutional partnerships. The analysis combines qualitative insights from diverse sources, including governmental reports, academic studies, and expert opinions. It explores the pre-Brexit landscape, identifies the core factors that shape the post-Brexit educational environment, and assesses the short-term and long-term consequences for educational institutions, students, and researchers in the UK.